Relationships between alumina and bauxite dust exposure and cancer, respiratory and circulatory disease. Issue 9 (19th March 2009) - Friesen, M C; Fritschi, L; Del Monaco, A; Benke, G; Dennekamp, M; de Klerk, N; Hoving, J L; MacFarlane, E; Sim, M R
Abstract : Objectives: To examine the associations between alumina and bauxite dust exposure and cancer incidence and circulatory and respiratory disease mortality among bauxite miners and alumina refinery workers. Methods: This cohort of 5770 males has previously been linked to national mortality and national and state cancer incidence registries (1983–2002). In this paper, Poisson regression was used to undertake internal comparisons within the cohort based on subgroups of cumulative exposure to inhalable bauxite and alumina dust. Exposure was estimated using job histories and historical air monitoring data. Results: There was no association between ever bauxite exposure and any of the outcomes. There was a borderline significant association between ever alumina exposure and cerebrovascular disease mortality (10 deaths, RR 3.8, 95% CI 1.1 to 13). There was some evidence of an exposure–response relationship between cumulative bauxite exposure and non-malignant respiratory disease mortality (seven deaths, trend p value: 0.01) and between cumulative alumina exposure and cerebrovascular disease mortality (trend p value: 0.04). These associations were based on very few cases and for non-malignant respiratory disease the deaths represented a heterogeneous mixture of causes. There was no evidence of an excess risk for any cancer type with bauxite or alumina exposure. Conclusions: These preliminary findings, based on very few cases, suggest that cumulative inhalable bauxite exposure may be associated with an excess risk of death from non-malignant respiratory disease and that cumulative inhalable alumina dust exposure may be associated with an excess risk of death from cerebrovascular disease. Neither exposure appears to increase the risk of incident cancers.